2021
DOI: 10.1021/acs.energyfuels.1c00973
|View full text |Cite
|
Sign up to set email alerts
|

Classification Evaluation of Gas Shales Based on High-Pressure Mercury Injection: A Case Study on Wufeng and Longmaxi Formations in Southeast Sichuan, China

Abstract: The physical properties of gas shales, especially the structural features of connected pore-fractures, are key parameters for evaluating shale gas resource potential and effective production. In this study, four major techniques, including mercury intrusion capillary pressure (MICP), low-temperature nitrogen adsorption/desorption (LT-NA/D) tests, scanning electron microscopy (SEM), and fractal theory, were adopted to establish a suitable pore size classification for gas shales from the Wufeng–Longmaxi formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…These organic matter pores were illustrated as ellipsoid to irregular polygons with diameters from several nanometres to hundreds of nanometres. Wei et al (2021) observed the organic matter pores were widespread and clustered in the organic‐rich samples cored from Wufeng and Longmaxi formations in south‐east Sichuan Basin, which were characterized by sponge‐like, elliptical and alveolate shapes with pore diameters ranging from 5 to 50 nm. Li et al (2021) showed the dominant pore shape in undeformed Wufeng‐Longmaxi shales were bubble‐like pores, spongy pores, static pores and randomly distributed pores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These organic matter pores were illustrated as ellipsoid to irregular polygons with diameters from several nanometres to hundreds of nanometres. Wei et al (2021) observed the organic matter pores were widespread and clustered in the organic‐rich samples cored from Wufeng and Longmaxi formations in south‐east Sichuan Basin, which were characterized by sponge‐like, elliptical and alveolate shapes with pore diameters ranging from 5 to 50 nm. Li et al (2021) showed the dominant pore shape in undeformed Wufeng‐Longmaxi shales were bubble‐like pores, spongy pores, static pores and randomly distributed pores.…”
Section: Discussionmentioning
confidence: 99%
“…It is also rapidly developed to investigate shale oil and shale gas resource distribution and strategic development in China (Chen et al, 2021; Liu et al, 2017; Wang, 2020; Wang et al, 2021). Spatial distribution, sedimentary evolution, organic geochemical characteristics, reservoir characteristics and shale gas accumulation mechanism of Palaeozoic marine shale have been widely studied in southern China (Cao et al, 2016; Liu et al, 2022; Wang et al, 2021; Wei et al, 2021; Zhang et al, 2022). Although Permian shale is also widely distributed in the south of China, its shale gas resource is rarely studied in the previous literature owing to unclear industrial value.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this, the grading evaluation criteria and the lower limit of formation of shale reservoirs are established and applied to the evaluation of target reservoirs. Combined with the research results of the author’s team in recent years, ,− ,, this paper reviews and summarizes the latest progress and development trends in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The pore size classification proposed by the International Union of Pure and Applied Chemistry in 1972 was widely accepted for chemical products and coal . However, it has limited applicability to HSR reservoirs, necessitating the establishment of an appropriate pore size classification standard.…”
Section: Introductionmentioning
confidence: 99%